Development of UI/UX E-Learning Javanese Android Apps Using User Centered Design (UCD) Method - Noptavia, Noptavia; Tarwoto, Tarwoto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Indonesia is a country with an area of 1.9 million km2 that is rich in diversity, including different languages in each region. This language diversity gives each region its own characteristics. However, in the 21st century, we witness the phenomenon of losing polite values in speaking using local languages. This is due to the influence of western culture that has penetrated Indonesia, especially through technological advances and television broadcasts that often show city and foreign cultures. One of the threatened cultures is the use of Javanese language which is increasingly rarely used. Javanese language is unique with unggah-ungguh as a differentiator from other regional languages. The rapid development of technology, especially in the world of education, requires that we make the best use of it, but still maintain and preserve ancestral heritage, such as Javanese. This research aims to design an optimal UI/UX design for Javanese E-Learning platform on Android device, focusing on UCD approach. Then after successfully designed, SUS calculation was done and obtained an average SUS value of 77.5 which means this design is good to continue to the application development stage. The target in this research is early childhood, researchers took the object of one of the MI in Banjarnegara Regency, namely MI Muhamadiyah Kalilandak.